Analyzing Bank Rakyat Indonesia's Financial Performance Using the CAMEL Method: Implications for Stability and Strategic Decisions in the Banking Industry - Roma Sinta Simbolon; Amran Manalu (Institute of Accounting Research and Novation (IARN), 2023)
Bank Rakyat Indonesia's (BRI) financial performance is evaluated using the CAMEL technique, a financial institution strength and stability framework. The report examines BRI's financial health, strengths, limitations, and effects on operations, stability, and strategy. The 2018–2022 study examines BRI's financial indicators. Capital Adequacy, Asset Quality, Management Quality, Earnings, and Liquidity are assessed to determine the bank's performance in each category. The report shows BRI's strengths and shortcomings, stressing its strong capital adequacy, asset quality, and management. It also highlights loan portfolio diversification, concentration risks, and regulatory compliance issues as issues. BRI's conformity with or exceeding industry benchmarks solidifies its status as a strong and reliable financial institution. The findings highlight the bank's importance in economic stability and growth, affecting lending capacity, service offerings, and stakeholder confidence. The study concludes that BRI's financial performance affects its operations, stability, and strategic decisions. The bank's excellent financial position strengthens its resilience, shapes its growth ambitions, and boosts its financial sector credibility, benefiting Indonesia's economy. This research shows BRI's strengths, shortcomings, alignment with industry norms, and how its financial performance affects its operations and strategic decisions, emphasizing its financial health.